Hubungan dukungan keluarga dengan harga diri remaja Di lembaga pemasyarakatan - Nelfice - -; Veny - Elita; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determine the relationship between family support and self-esteem of adolescent in prison. This research used descriptive correlative method with cross-sectional approach. Samples of this research were taken using purposive sampling. This research’s sample consists of 57 adolescents in Lembaga Pemasyarakatan Kelas II B Pekanbaru. Data was collected using Ronsenberg self esteem (1995) by Ronsenberg and a questionnaire modified from Khalid (2011). And then it was analyzed using fisher's exact test. The results showed that the numbers of adolescent who have high social support and have high self esteem are 29 respondents (100%). While, the numbers of adolescent who have low social support and have high self-esteem are 27 respondents (96.4%). From the result, it can be concluded that there was no relationship between family support and self-esteem of adolescent in prison (p value = 0.491> α 0.05). Based on this study, it is suggested to the families to provide high social support to adolescents in prison, so that they can survive or adapt to the needs and experience during their training in prison, rediscover their confidence, and could be a part of community members when they are free. Keywords: Adolescent, family support, prison, self-esteem References: 79 (2003-2013)